2021
DOI: 10.1038/s41598-021-01287-2
|View full text |Cite
|
Sign up to set email alerts
|

Heightened effort discounting is a common feature of both apathy and fatigue

Abstract: Apathy and fatigue have distinct aetiologies, yet can manifest in phenotypically similar ways. In particular, each can give rise to diminished goal-directed behaviour, which is often cited as a key characteristic of both traits. An important issue therefore is whether currently available approaches are capable of distinguishing between them. Here, we examined the relationship between commonly administered inventories of apathy and fatigue, and a measure of goal-directed activity that assesses the motivation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 84 publications
3
13
0
Order By: Relevance
“…This reflects a greater subjective cost of effort execution, which parallels the observation that increased fatigue also is related to reduced efforts to engage in social interactions (Slavich & Irwin, 2014). Similar findings of increased subjective costs for physical effort are typically observed in clinical samples (Jurgelis et al, 2021; Tran et al, 2021) and have been interpreted as an adaptive bodily response to exhaustion. This is also supported by our finding that state changes of fatigue did not have detrimental consequences in terms of performance outcome.…”
Section: Discussionsupporting
confidence: 77%
“…This reflects a greater subjective cost of effort execution, which parallels the observation that increased fatigue also is related to reduced efforts to engage in social interactions (Slavich & Irwin, 2014). Similar findings of increased subjective costs for physical effort are typically observed in clinical samples (Jurgelis et al, 2021; Tran et al, 2021) and have been interpreted as an adaptive bodily response to exhaustion. This is also supported by our finding that state changes of fatigue did not have detrimental consequences in terms of performance outcome.…”
Section: Discussionsupporting
confidence: 77%
“…Lower motivation has been proposed to be a central feature of both apathy and fatigue 4,49,81 . More specifically, both constructs have been associated with distorted effort-based decision-making 82 , and appear to implicate similar neural circuits involved in valuation and reward processing [83][84][85] . In the present study, fatigue ratings were collected in order to track the development of fatigue throughout the experiment.…”
Section: Apathy Is Expressed As a Decoupling Of Reward And Fatiguementioning
confidence: 97%
“…12 Apathy has also been shown to be associated with components of frailty, such as physical activity and fatigue. 13,14 In addition, the presence of apathy has been reported to lead to a decline in executive function, 9,15 which may be a factor influencing the development of frailty. 16 These findings suggest reciprocal associations between apathy and frailty, but to our knowledge, only two studies have examined these association in community-dwelling older adults 17,18 and both focused only on physical frailty.…”
Section: Introductionmentioning
confidence: 99%
“…A previous review has shown there is much evidence that apathy is associated with declines in physical function, cognitive function, and activities of daily living (ADL) 12 . Apathy has also been shown to be associated with components of frailty, such as physical activity and fatigue 13,14 . In addition, the presence of apathy has been reported to lead to a decline in executive function, 9,15 which may be a factor influencing the development of frailty 16 .…”
Section: Introductionmentioning
confidence: 99%